Teaching maintenance of medical devices in simulation centers: a pilot study (2016)
This paper aims to measure what the students’ perceived learning outcome achievements are after finishing medical devices courses I and II. This is a pre- post-test with no control group study design. Twenty-four students doing medical devices courses I and II with a test in the simulation center of a Biomedical Engineering Program participated in this pilot study. A paper-based survey composed of a demographic and 5-point Likert (“1” is strongly disagree and “5” is strongly agree) measured the students’ perceived learning outcome achievements after exposing them to medical devices courses. A Wilcoxon signed-rank test and Mann-Whitney U Test statistics were conducted to test the two hypotheses of this study. Our analysis showed statistically significant results between the pre-survey sum mean and SD: 7.50, 1.31; and between the post-survey mean and SD: 8.56, 1.15, p=0.015, indicating the students’ perceived learning outcome achievements after putting them through medical devices courses I and II had significantly improved by the end of the courses. Also, no statistically significant results were found between the post-survey mean and SD: 4.37, 0.57 learning outcome perceptions or between the students’ actual marks mean and SD: 4.58, 0.18, p=0.28), indicating no differences between what the students perceived they had learned compared with what they had really learned.